LEGAL PROTECTION OF WAKAF ASSETS IN INHERITANCE DISPUTES - Salmawati; Yusuf, Muh Rayhan Fahrizal (Pena Cendekia Insani, 2026)
This study aims to analyze the form of legal protection for waqf assets that are the object of inheritance disputes from the perspective of Indonesian positive law and Islamic legal principles. The focus of this research lies in the legal regulations that guarantee the continuity of the status of waqf assets so that they do not return to being part of the inheritance that can be claimed by the heirs. This study uses a normative legal research method with a statute approach and a conceptual approach. The data used are in the form of primary, secondary, and tertiary legal materials obtained through literature studies, then analyzed qualitatively using descriptive-analytical methods to understand the relationship between applicable legal norms and waqf dispute issues in practice. The results of the study indicate that the legal system in Indonesia provides strong legal protection for waqf assets through the recognition of changes in ownership status after the waqf pledge, the prohibition of transfer or inheritance of waqf assets as regulated in Law Number 41 of 2004 concerning Waqf, and supervision of waqf management by nazhir and state institutions such as the Indonesian Waqf Board. Furthermore, Islamic legal principles such as ta?b?s al-a?l wa tasb?l al-manfa ‘ah and protection of the will of the waqif are important foundations for maintaining the sustainability of waqf benefits for the community. This study also found that waqf disputes related to inheritance are generally triggered by weak waqf administration and a lack of public understanding of the principle of waqf permanence. The implications of this study demonstrate the importance of strengthening the waqf administration system, increasing public legal literacy, and optimizing the role of waqf management institutions to ensure legal certainty and the sustainability of waqf's social function as an instrument of public welfare.